Analisis kadar mineral mikro tembaga dan besi pada biji durian - Ayu Lestari; Irwan Said (Media Eksakta, 2023)
This study aims to determine the levels of copper and iron contained in durian seeds, determine the levels of copper and iron using Atomic Absorption Spectrophotometer (AAS). The results showed that the analysis of the water content of durian seeds obtained 37.382%, ash content 17.782% and mass 44.835%. Analysis of the iron content measured at the copper wavelength of 248,3 nm, at the wavelength of 249,2, the results obtained respectively 49.244 ± 116.076 mg/100g for copper and 66.495± 15.753 mg/100g for iron. The results of this study are expected to be one of the alternative food ingredients that can be processed into food to meet the copper and iron substances in the body.